2018
DOI: 10.1073/pnas.1720342115
|View full text |Cite
|
Sign up to set email alerts
|

Mavacamten stabilizes an autoinhibited state of two-headed cardiac myosin

Abstract: We used transient biochemical and structural kinetics to elucidate the molecular mechanism of mavacamten, an allosteric cardiac myosin inhibitor and a prospective treatment for hypertrophic cardiomyopathy. We find that mavacamten stabilizes an autoinhibited state of two-headed cardiac myosin not found in the single-headed S1 myosin motor fragment. We determined this by measuring cardiac myosin actin-activated and actin-independent ATPase and single-ATP turnover kinetics. A two-headed myosin fragment exhibits d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
158
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(184 citation statements)
references
References 41 publications
24
158
2
Order By: Relevance
“…Interestingly, our data also show that Myk461 incubation significantly slowed k rel in the KO myocardium but not in the WT myocardium, effectively normalizing the basal differences in k rel between KO and WT groups (Table 3; Figure 5), suggesting a slowing in the strain‐induced XB detachment from actin in the KO myocardium. Our observation of unaltered k rel in WT myocardium agrees with results from solution‐based transient kinetic studies, which show that Myk461 does not affect the ADP release rate from actomyosin 22, 48. However, our result that Myk461 slows XB detachment in KO indicates a differential impact of Myk461 on XB detachment, suggesting that the impact of Myk461 may vary depending on the presence or absence of cMyBPC in an intact sarcomeric lattice system that is influenced by strain‐dependent mechanisms, a phenomenon that is difficult to replicate using solution‐based transient kinetic studies.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Interestingly, our data also show that Myk461 incubation significantly slowed k rel in the KO myocardium but not in the WT myocardium, effectively normalizing the basal differences in k rel between KO and WT groups (Table 3; Figure 5), suggesting a slowing in the strain‐induced XB detachment from actin in the KO myocardium. Our observation of unaltered k rel in WT myocardium agrees with results from solution‐based transient kinetic studies, which show that Myk461 does not affect the ADP release rate from actomyosin 22, 48. However, our result that Myk461 slows XB detachment in KO indicates a differential impact of Myk461 on XB detachment, suggesting that the impact of Myk461 may vary depending on the presence or absence of cMyBPC in an intact sarcomeric lattice system that is influenced by strain‐dependent mechanisms, a phenomenon that is difficult to replicate using solution‐based transient kinetic studies.…”
Section: Discussionsupporting
confidence: 88%
“…It has been shown that myocardial samples isolated from HCM patients expressing cMyBPC mutations often display reduced total cMyBPC expression7, 25 and accelerated XB kinetics27; therefore, we sought to investigate the effects of Myk461 on the contractile function of myocardium lacking cMyBPC. In this context, recent data show that Myk461 stabilizes an autoinhibited state of 2‐headed myosin structure48 and also strengthens a folded‐back sequestered super‐relaxed state of myosin heads onto the thick filament backbone49—an effect that contributes to Myk461‐induced force depression by stabilizing the “ off ” state of myosin heads and preventing acto‐myosin formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anderson et al showed that the level of SRX measured by mant-ATP single turnover by WT 25hep HMM corresponds well to a folded-back state of the 25-hep WT HMM, as observed by negative staining electron microscopy 24 . To investigate whether the HCM mutations R249Q and H251N release sequestered myosin heads into a functionally active state, we used mant-ATP single turnover kinetics, a technique originally used to probe the level of SRX in cardiac myosin fibers 41,42 which has more recently been applied to purified cardiac myosin 24,44 . When bound to myosin, mant-ATP shows increased fluorescence.…”
Section: Hcm Mutations On the Myosin Mesa Of 25-hep Hmm Lead To A Gaimentioning
confidence: 99%
“…The potential importance of a folded-back sequestered state of cardiac myosin has recently been highlighted in diseases like HCM, and also in the mechanism of action of cardiac inhibitors like mavacamten (15,37,38). The cardiac activator omecamtiv mecarbil has also been shown to stabilize the open state of cardiac myosin while also impacting the kinetics of actin-bound myosin motors (39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%